Optimum predictors of childhood asthma: persistent wheeze or the asthma predictive index? - Amin, Priyal (J Allergy Clin Immunol Pract, 2014)
BACKGROUND: The Asthma Predictive Index (API) and persistent wheezing phenotypes are associated with childhood asthma, but previous studies have not assessed their ability to predict objectively confirmed asthma. OBJECTIVE: To determine whether the University of Cincinnati API (ucAPI) and/or persistent wheezing at age three can accurately predict objectively confirmed asthma at age seven. METHODS: Data from the Cincinnati Childhood Allergy and Air Pollution Study (CCAAPS), a high risk prospective birth cohort, was used. Asthma was defined as: parent-reported or physician-diagnosed asthma objectively confirmed by a change in FEV1 of ≥ 12% post bronchodilator or a positive methacholine challenge (PC(20) ≤ 4 mg/ml); or prior treatment with daily asthma controller medication(s). Multivariate logistic regression was used to investigate the relationship between confirmed asthma at age seven and a positive ucAPI (adapted and modified from prior published API definitions) and persistent wheezing at age three. RESULTS: At age seven, 103 of 589 (17.5%) children satisfied the criteria for asthma. Confirmed asthma at age seven was significantly associated with a positive ucAPI (adjusted [a]OR=13.3; 95% CI [7.0–25.2]; p<0.01) and the persistent wheezing phenotype (aOR = 9.8 [4.9–19.5]; p <0.01) at age three. Allergic persistent wheezing was associated with a significantly higher risk of asthma (aOR = 10.4 [4.1–26.0]; p<0.01) than non-allergic persistent wheezing (aOR = 5.4 [2.04–14.06]; p <0.01). CONCLUSIONS: Both a positive ucAPI and persistent wheeze at age 3 years were associated with objectively confirmed asthma at age seven; however the highest risk was associated with ucAPI. These results demonstrate that the ucAPI as a clinically useful tool for predicting future asthma in school-age children.